2017
DOI: 10.1096/fasebj.31.1_supplement.579.2
|View full text |Cite
|
Sign up to set email alerts
|

Restoring dinosaur cephalic vascular anatomy and thermophysiology using osteological correlates and anastomotic connections

Abstract: The restoration of dinosaur cephalic blood vessels is critical to understanding physiological thermoregulatory strategies in dinosaurs. Cephalic blood vessels of extant diapsids are known to support physiological thermoregulatory capabilities that modulate head and neurosensory tissue temperatures. Given their close phylogenetic relationship to extant diapsids, dinosaurs are hypothesized to have had similar vascular arrangements and physiological abilities. To test this hypothesis, the cephalic vascular anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Gross dissections revealed that only blood vessels passed through the foramen (Porter and Witmer, ; Porter et al, ). Saurischian dinosaurs had a similar osteological correlate, which is also hypothesized to only contain blood vessels (Porter, ). Likewise, only vascular components (the palatine artery and vein) traverse the suborbital fenestra in extant diapsids, and there is no evidence from the fossil record of extinct dinosaurs to indicate that they were any different in this regard.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Gross dissections revealed that only blood vessels passed through the foramen (Porter and Witmer, ; Porter et al, ). Saurischian dinosaurs had a similar osteological correlate, which is also hypothesized to only contain blood vessels (Porter, ). Likewise, only vascular components (the palatine artery and vein) traverse the suborbital fenestra in extant diapsids, and there is no evidence from the fossil record of extinct dinosaurs to indicate that they were any different in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…The palatomaxillary vessels gave off the palatine vessels (which then pass through the small suborbital fenestra) dorsal to the ectopterygoid and then entered the dorsal alveolar canal as the maxillary vessels in the rostroventral aspect of the orbit (Fig. ; Porter, ). The dorsal alveolar canal passed ventral to the rostral loop of the airway (Witmer and Ridgely, ), where the roof of the canal was not detectable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations